Sense of Belonging and Community Building within a STEM Intervention Program: A Focus on Latino Male Undergraduates' Experiences. (April 2022) - Abrica, Elvira J.; Lane, Tonisha B.; Zobac, Stephanie; Collins, Elizabeth
Relying on semi-structured, qualitative interviews with 13 Latino male undergraduates in engineering, this study explored students experiences and sense of belonging within a Minority Retention Program at a 4-year public university in California. Findings support extent research on the importance of structural interventions in science, technology, engineering, and mathematics (STEM) while highlighting nuance in experiences of Latino males, including perceptions of stigma associated with participation. Implications for future research and practice are discussed.